Remobilization of Heavy Metals by Mangrove Leaves - Almahasheer, Hanan; Serrano, Oscar; Duarte, Carlos M.; Irigoien, Xabier (Frontiers in Marine Science, 2018)
Several studies have been carried out on heavy metal pollution in mangrove ecosystems. However, the role of mangroves in heavy metal remobilization is still relatively unknown. On one side, mangrove woody organs and soils sequester heavy metals for long time periods, but on the other hand, senescence of mangrove leaves may return these metals collected by roots to the upper layers of the soil. Here, we analyzed the concentration of chemical elements (Al, As, Cd, Cr, Cu, Fe, Mn, Mo, Ni, Pb, Sr, V and Zn) as a function of age in mangrove leaves to understand heavy metals retention by the plant and to quantify the amounts shed with senescing leaves. In addition, we estimated metal concentrations and stocks in mangrove soils. Our results revealed that the concentration of most metals increased with leaf age, resulting in the remobilization of metals stored in soil, thereby returning metals to the upper layers of the soil during senescence of mangrove leaves. Only Cu was reabsorbed prior to shedding of leaves, a mechanism similar to that described for nutrients in mangroves globally. These results provide key data to understand mangroves role in the dynamics of heavy metals.